The Citations of Apollonius Rhodius’ Argonautica in Angelo Poliziano’s Unpublished Hand Notes to Virgil’s Aeneid - Vespoli, Lorenzo (Sapiens ubique civis, 2023)
As far as scholars know from the available evidence, Angelo Poliziano’s academic activity in the Studium of Florence did not include a course specifically devoted to Apollonius Rhodius. This paper offers a survey of the citations from Apollonius Rhodius’ Argonautica in Poliziano’s hand notes to the Aeneid, transmitted by the incunabulum Paris, BNF, Rés. G. Yc. 236, to provide new information for further research both on the humanist’s interest in the Hellenistic poem and, more generally, on the Apollonian reception in the Renaissance.